Oncogenic hijacking of a developmental transcription factor evokes vulnerability toward oxidative stress in Ewing sarcoma - Marchetto, Aruna; Ohmura, Shunya; Orth, Martin F.; Knott, Maximilian M. L.; Colombo, Maria V.; Arrigoni, Chiara; Bardinet, Victor; Saucier, David; Wehweck, Fabienne S.; Li, Jing; Stein, Stefanie; Gerke, Julia S.; et al. (Nature Communications, 2020)
Ewing sarcoma (EwS) is an aggressive childhood cancer likely originating from mesenchymal stem cells or osteo-chondrogenic progenitors. It is characterized by fusion oncoproteins involving EWSR1 and variable members of the ETS-family of transcription factors (in 85% FLI1). EWSR1-FLI1 can induce target genes by using GGAA-microsatellites as enhancers.